El cuento tradicional en el desarrollo de la atención de los niños y niñas de 1 a 3 años del centro infantil del buen Vivir “Corazón Alegre” periodo 2016 - Valente Conya, María Juliana (2017)
The present research entitled: Traditional Stories in the development of children aged 1 to 3 years in “Centro Infantil del Buen Vivir Corazon Alegre” in 2016, it is determined with the aim of improving the concentration of students through the application of various activities that contain pictograms, puppets and dramatizations, which have provided very motivating actions for the enrichment of their adaptation and training. For this reason, it began with the development of the theoretical framework, which includes the scientific basis, relating to the independent variable that refers to traditional stories and dependent attention with their respective contents, highlighting concepts, importance, characteristics, in addition to others topics of interest to this process. The methodological framework, focused on the design that is quasi experimental and correlational, types of research, explanatory-descriptive, field research and bibliographical, the methods applied: the hypothetic-deductive, analytical-synthetic, the technique applied was the observation, supported by charts as an instrument, the population of study was defined only with children from 1 to 3 years. Subsequently, activities were carried out with narratives of traditional stories in order to progressively improve the behavior of infants in and out of the classroom. With the data obtained in the observation to the students, statistical tables and graphs were organized to perform the analysis and interpretation of results, concluding with the verification of specific hypotheses and then determining the conclusions and recommendations. The results obtained through the application of various activities that motivated children to develop their attention capacity, also achieving habits of self-discipline, expression of feelings and emotions, knowing the characteristics of different characters or animals and recognizing the importance of active participation individually and in groups KEY WORDS: Behavior, determined, pictograms, emotions